Health sector analysis: political economy of decentralised health service provision - MAP Consult; Konung International (POTENCIAR, 2021)
This report offers POTENCIAR and the British High Commission (BHC) an analysis of how power arrangements influence the main social, political, and economic factors in service provision and decentralised governance in Mozambique. The results of the study will be used to refine POTENCIAR’s strategy and approach, as well as the design of PAIs in the health sector. While PAIs address issues across multiple sectors, sector analysis will also consider potential entry points for, as well as barriers to, the improvement of intersectoral coordination and strengthening of citizen participation. Through an analysis of the political economy of the health sector, this report will examine the formal and informal power structures and institutions that influence service provision and the decentralised governance of the health sector. Methodologically, the study is based on a bibliographic and documentary review of governance, decentralisation, and accountability across Mozambique, and the health sector in particular. These data are complemented by interviews with key informants who have knowledge of or actively participate in the health sector. The study is based on the northern province of Nampula, which POTENCIAR has identified for the implementation of its first pro-accountability initiative in the health sector.
Keywords: *non-public; G - Mozambique / Moçambique; GP - Nampula; Health PEA; L - english / inglês; access to services / acesso a serviços; accountability / responsabilização; health - health services / serviços de saúde; health / saúde

State Budget Proposal for Fiscal Year 2020 – Mozambique, Analysis of the Social and Economic Sectors - UNICEF (UNICEF Mozambique, 2020)
Key messages: 1. The value of the State Budget for 2020 is MT 345.4 b. The 2020 State Budget marks the beginning of a new governance cycle (2020-2024) and is aligned with the strategic objectives and priorities defined in the new 5-year plan (PQG 2020-2024). However, the current global COVID19-induced economic uncertainty has led the Government of Mozambique to a restrictive approach to the budget aimed at prioritizing the provision of basic services to the population. 2. The Council of Ministry’s Decree n.2/2020 established the principles and norms of the provincial decentralized governance, both political and financial. However, this was not yet reflected in 2020 State Budget. 3. The government’s new overarching development strategy, the “Government’s Five-Year Plan (PQG 2020-2024)” has 3 strategic priorities and 3 strategic pillars. In the 2020 State Budget, Priority II: Promote Economic Growth, Productivity and Job Creation, received the majority of funding, worth 44 percent of budget. Priority I: Develop Human Capital and Social Justice was allocated 35 percent of 2020 State Budget resources. 4. This year the Government has prioritized the allocation of resources to essential sectors, namely Health, Education and Agriculture & Rural Development. The allocation to these three sectors is worth 48 percent of 2020 State Budget (excluding debt servicing and financial operations) or 34 percent of the entire budget. Relative to last year, the allocation to the Education sector increased while those of the Health and Agriculture sectors decreased. 5. In the 2020-2024 PQG, the Government set the goal of allocating 65.2 percent of resources to priority economic and social sectors. This year’s cumulative allocation to priority areas is worth 68 percent of the State Budget less financial operations and debt servicing, or 48 percent of the entire State Budget including financial operations and debt servicing. Of the priority Economic and Social sectors supported by UNICEF, Education was allocated Meticals (MT) 66.3 billions (b), Health MT 26.7 b, Social Action MT 6.7 b and WASH MT 7.1 b in the State Budget for 2020. 6. The allocation to Education increased by 17 percent in nominal terms and by 9 percent in real terms relative to 2019 Budget. The sector allocation is worth 19.2 percent of 2020 State Budget. Excluding financial operations and debt servicing, education represents 27.1 percent. As a share of Mozambique’s GDP, the Education sector’ allocation represents 6.1 percent. 7. The Health allocation represents a 5 percent nominal decrease and an 11 percent real terms-decrease compared to last year’s budget. Such decrease is explained by the heavy reduction in externally-funded on-budget resources to the sector. Health is worth 7.7 percent of the 2020 budget. Excluding financial operations and debt servicing, the sector represents 10.9 percent. As a share of the expected GDP for 2020, the Health Budget is worth approximately 2.5 percent. Relative to last year, the sector allocations decreased both as a share of government expenditure and as a share of GDP. 8. The Ministry of Health has developed a National Plan for COVID-19 preparedness and response which will be allocated approximately MT 1.8 b or USD 28.4 m through off-budget resources, of which 56 percent will be allocated to drugs and supplies. The Ministry of Health COVID-19 Plan however does not include budget for water services and hygiene measures essential to Infection prevention and control (IPC). 9. The 2020 initial allocation to Social Action dropped by 7 percent in nominal terms and by 14 percent in real terms compared to 2019. However, spending for INAS Social Protection Programs as a share of budget and as a share of GDP is on par with those of last year. Still, given the risk of increased vulnerabilities due to COVID-19, larger allocations to INAS programs are recommended.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; budget / orçamento

State Budget Proposal for Fiscal Year 2019 – Mozambique, Analysis of the Social and Economic Sectors - UNICEF (UNICEF Mozambique, 2019)
Key messages: 1. The envelope of resources for the 2019 State Budget is set to increase to MT 340 billion (from MT 303 billion in 2018), representing Mozambique’s largest nominal budget; however, once factoring in the depreciated currency and high inflation of recent years as well as high debt servicing payments, the purchasing power of this envelope –including for priority sectors– no longer represents a historical high. 2. The share of resources dedicated to investment in Mozambique has been steadily declining, particularly since 2015, due to frozen donor support and a crowding out effect by proportional increases in financial operations and recurrent spending. While in the 2019 Budget Proposal investment has increased to a 30 percent share of total spending, it is still far below the 40 percent norm registered a decade ago. 3. Over the past decade, the share of resources dedicated to the district level has increased at the expense of resources directed to the provincial level; meanwhile central-level expenditure has remained unchanged. In the 2019 Budget Proposal, the central level will, as usual, receive the most resources (64 percent), followed by districts (19 percent), provinces (15 percent), and then municipalities (2 percent). 4. Relative to the Government’s Five Year Plan (PQG), “Priority II: Develop Human and Social Capital” (i.e. priority economic and social sectors) is expected to receive the largest share of funding in the 2019 Budget Proposal. 5. The government has set the goal of allocating at least 60 percent of resources to the priority sectors (according to its methodology of excluding financial operations and debt servicing from the denominator); however, because financial operations and debt servicing have soared as a share of total spending, their 60 percent is no longer a reliable benchmark (e.g. priority sector allocations grew 3.5 times in nominal terms from 2009 to 2019 while the entire budget grew 4 times over the same period) . Proportional priority sector spending as a share of the entire budget (including financial operations and debt servicing) has dropped significantly in recent years. In the 2019 Budget Proposal, it is projected at 51 percent of the entire budget. 6. Among Priority Economic and Social Sectors, Water & Public Works, Transport & Communications, and Agriculture & Rural Development more than doubled their proposed allocations for 2019 relative to 2018 initial allocations. The Education, Health, and Social Action Sectors are also expected to receive a larger allocation than in 2018, but the increase will be smaller. The Infrastructure Sector (mainly the roads sub-sector) will be the only one experiencing a cut in allocation relative to the 2018 Budget.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; budget / orçamento

For an efficient, decentralised, transparent and inclusive health system - N'weti (N'weti, 2016)
Recommendations: 1. On planning and budgeting, greater coordination is recommended between planning (setting priorities) and budgeting (financial apportionment). Transformation of all District Health Services, Women and Social Action (SDSMAS) into Management Beneficiary Units (MBU) is necessary. 2. Stakeholders should bet more on application of national public financial management systems (PFM). The use of parallel financial systems instead of enabling the National Health System (NHS) to be more e cient hinders the enhancement of the sector’s PFM systems. 3. With regard to budgeting, zero-based budgeting implementation is recommended, replacing the incremental budgeting system. Zero-based budgeting is more realistic in so far as the health sector operation costs are concerned. 4. On the decentralisation and citizen participation component, the establishment of a national plan for decentralisation in the health sector is recommended. This plan would allow systematise local citizen participation mechanisms in the health system management and monitoring. 5. On revenue collection, the sector authorities need to explore areas of potential revenue already identified in Intellica’s 2013 research report, such as drug prescription, outpatient, medical certificate rates; and comply with the Decree 11/2007 of 30 May, which regulates tobacco consumption and sale, which has great potential to generate revenue for the health sector at the district level, by means of fines on the lawbreakers. 6. A Policy Brief drawn from the Public Expenditure Tracking Survey (PETS) in the Health Sector in Angoche, Bilene, Magude and Xai-Xai districts, and Chamanculo and José Macamo General Hospitals On expenditure performance, more and better coordination among stakeholders at district levels and Health Centres is recommended in order to avoid expenditure implementation costs in a fragmented and uncoordinated manner. 7. On procurement, accuracy improvement is recommended for the current legal framework implementation. This is to ensure that Procurement Management Units (PMUs) are practical; they can perform their tasks with independence, impartiality and professionalism. The direct award should always be treated as provided for in the law (an exception) and not deemed as the rule like what we have noticed occur in the researched cases. The document disorderliness of the Procurement Management Units portfolios can be solved with portfolio digitisation, ensuring more and better file and document handling, more control and additional transparency. 8. On transparency, recommendation to the Ministry of Health (MoH) is on the establishment of mechanisms which may ensure that sector o cials, who handle equal duties, should have the same understanding about procedures, not only in the health sector, but also in liaison with other sectors and society in general. When applying the Right to Information Act, Civil Society Organizations (CSOs) should now carry out awareness raising sessions and dialogue with sector o cials in order to reach mutual understanding on the added value that represents transparent public service management, with accountability and civil society influence, through monitoring and evaluation.
Keywords: *indexed; *non-public; *tagged; G - Mozambique / Moçambique; G - north / norte; GD - Angoche; GD - Bilene; GD - Magude; GD - Xai-Xai; GP - Nampula; Health PEA; Important; L - english / inglês; access to services / acesso a serviços; accountability / responsabilização; budget / orçamento; decentralization / descentralização; health / saúde

Relatório para o Governo da Província de Cabo Delgado e Agência Espanhola de Cooperação Internacional para o Desenvolvimento (AECID) - Umarji, Mariam; Makda, Sadya; Paulo, Arsénio; Lalá, Aly (SAL & Caldeira, 2009)
O relatório que se segue retrata a avaliação conduzida ao Sistema de Gestão de Finanças Públicas da Província de Cabo Delgado considerando o ciclo orçamental do ano de 2008, considerando a informação de contabilidade, reporte e auditoria relacionada com este ano mas produzida em 2007 e em 2009. A avaliação teve como base a Metodologia PEFA – Despesa Pública e Responsabilidade Financeira – devidamente adaptada ao nível subnacional (província) de acordo com as orientações metodológicas emanadas pelo Secretariado PEFA. Foram utilizados um total de 25 indicadores para a avaliação. Os indicadores reflectem a situação actual do sistema e fornecem um ponto de comparação para avaliações ou seguimentos futuros dos progressos esperados nos processos de planificação, orçamentação, contabilidade, reporte e auditoria da província. Esta Avaliação Sumária apresenta as constatações finais da equipa de consultores sendo fruto do trabalho de campo realizado para inquérito e recolha de evidência combinada com a revisão documental de informação recebida e disponibilizada de forma a se poder realizar a avaliação dos diferentes indicadores.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - portuguese / português; budget / orçamento; fiscal policy / política fiscal

A gender analysis of the impact of indirect taxes on small and medium enterprises in Vietnam - Akram-Lodhi, A Haroon; van Staveren, Irene (Institute of Social Studies, 2003)
This paper brings together gender analysis, small scale enterprise analysis, and gender budget analysis in a development context. The paper demonstrates that gender matters not only to the ownership of an SME, but also to its most likely principal activity, the stock of the assets that it possesses, the labour that it utilizes, the costs that it faces, the revenues that it generates, and the profits that it earns. In particular, lower earnings for female-owned SMEs can be attributed to the different input cost structures facing female and male-owned SMEs, which in turn are influenced by the indirect tax system. In this context, the paper identifies five gender biases in Vietnam’s VAT system. These biases help explain the higher costs and lower profits of female-owned SMEs in Vietnam. This explanation is different from the more common explanation given for lower performance of female owned enterprises in developing countries, which is the gender segregation of sectors. Although this also plays a role, we argue that gender biases in costs and earnings, partly caused by the tax system, are the more dominant factor.
Keywords: G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA; budget / orçamento; gender / género

Deviations between the Planned and the Execution Undermine the Health Budget – Observatório do Cidadão para Saúde - Observatório Cidadão para Saúde
In Mozambique, health services are mostly provided by the public sector, and it is the responsibility of the Ministry of Health (MISAU) to enable the creation, planning and control of national health policies. The health sector is the third sector that absorbs most resources from the State Budget (OE), followed by the Education and Infrastructure sectors, according to the methodology presented in the budget documents related to the economic and social sectors. This sector is divided into three levels: namely, the Central Level, which is represented by MISAU; The Provincial Level, which is represented by the Provincial Health Directorates (DPS); and Finally, we have the District Level, which is represented by the Health, Women and Social Action Secretariats (SDSMAS). Therefore, it will be based on these levels that our analysis of allocations to the health sector in the period from 2015 to 2020 will be undertaken.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; budget / orçamento; health - health services / serviços de saúde